2019
DOI: 10.1111/ipd.12475
|View full text |Cite
|
Sign up to set email alerts
|

The psychometric properties of the CFSSDS for schoolchildren in Saudi Arabia: A confirmatory factor analytic approach

Abstract: Summary Aim To test the psychometric properties of an Arabic version of the Child Fear Survey Schedule‐Dental Subscale (CFSS‐DS) a using confirmatory factor analysis. Methods Two convenience samples were obtained: Sample [1]: 600 boys (33%) and girls attending 4 public schools in Onizah and Sample [2] 800 girls attending 8 public schools in Buridah. The questionnaire asked the participant's age, gender, and completion of the CFSS‐DS. The data were subjected to exploratory factor analysis (EFA), parallel factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…7,23 Therefore, given the correct help, the children in the study showed promise in overcoming their fears and anxieties associated with dental appointments. 37 The obtained results were consistent with results obtained by Alharbi et al 20 , who found that Saudi children aged 8-15 years showed moderate CFSS-DS scores, proving the reliability of the Arabic translation of CFSS-DS to evaluate the child's dental fear and anxiety. The results also agreed with Kvesić et al 38 , who found that children aged 8-13 years have moderate CFSS-DS scores in Croatian children who suffered traumatic dental injury.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…7,23 Therefore, given the correct help, the children in the study showed promise in overcoming their fears and anxieties associated with dental appointments. 37 The obtained results were consistent with results obtained by Alharbi et al 20 , who found that Saudi children aged 8-15 years showed moderate CFSS-DS scores, proving the reliability of the Arabic translation of CFSS-DS to evaluate the child's dental fear and anxiety. The results also agreed with Kvesić et al 38 , who found that children aged 8-13 years have moderate CFSS-DS scores in Croatian children who suffered traumatic dental injury.…”
Section: Discussionsupporting
confidence: 85%
“…The principal investigator evaluated the level of dental anxiety in every participant child prior to each dental visit using the Arabic-validated version of the Children's Fear Survey Schedule Dental Subscale (CFSS-DS). [20][21][22] Each query response received a numerical value ranging from 1 (representing no fear) to 5 (representing extreme dread); the cumulative score for each child varied from 15 to 75. Pediatric individuals who achieved a CFSS-DS score of 38 or above were categorized as having dental anxiety.…”
Section: Dental Fear and Anxiety (Dfa)mentioning
confidence: 99%
“…The second section comprised items to report the oral hygiene habits of children, and the final section comprised the Children Fear Survey Schedule—Dental Subscale (CFSS-DS) to score the dental fear of children. This scale was selected due to the ease of administration and also because its Arabic version was subjected to psychometric analyses [ 12 ]. Dental fear was assessed using 15 questions broadly concerning “dentists”, “injections”, and “opening the mouth”.…”
Section: Methodsmentioning
confidence: 99%
“…3 Identifying high levels of anxiety is important for everyone involved in pediatric dental care. 4 This is important so that the staff can anticipate negative behaviors and reactions and minimize the need for further measures to be implemented to make the dental treatment less problematic. 5 Among the psychometric methods available for assessing dental anxiety and fear in children and adolescents, the Children's Fear Survey Schedule-Dental Subscale (CFSS-DS) is the most widely used.…”
Section: Introductionmentioning
confidence: 99%
“…6 This scale was developed by Scherer and Nakamura 7 and modified by Cuthbert and Malamed. 8 It has been validated by several countries, including Sweden, 9 Greece, 10 China, 11 Italy, 12 Saudi Arabia, 4 and Brazil. 13 Dental anxiety is not considered to be stable, 14 since some factors may influence it over time, such as behavior during dental treatment and some components of dental history, including dental caries experience and types of previous dental treatments received.…”
Section: Introductionmentioning
confidence: 99%